Hubungan Kinerja Perawat dengan Kepuasan Pasien di Rawat Inap RS Bhayangkara Tk. II Jayapura - Cresensia Kanip Kurupat; Nutrisia Nu’im Haiya; Moch. Aspihan (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Background: Nurses are the most dominant health workers in hospitals including inpatient installations. This dominance tends to have an impact on the main focus of the community including patients. When the nurse's performance is good, being able to cover all services in the hospital will be of good value in the eyes of the community and patients, making it a crucial point for nurses to work in accordance with the competencies, main tasks and functions and practice standards set by health care facilities. This study examines the relationship between nurse performance and patient satisfaction treated at the inpatient installation of Bhayangkara Hospital Jayapura. Method: This study is a type of non-experimental quantitative research with correlation studies. Data collection was carried out using questionnaires. The number of respondents was 98 people with the same number of nurses and patients, namely 49 people. The sampling technique used was incidental. Data were analyzed using spearmank rho. Result: Based on the results of the study, it was found that the age of 26-45 years, female, with a Diploma III education, and a length of work of more than 3 years. While the majority of patient respondents were aged 18-25 years, female, with the most education being high school, having a self-employed job, and a length of care of 1-3 days. The performance of nurses found to be categorized as good while the majority of patient satisfaction was very satisfied. The results of the spearman rho analysis obtained a correlation strength level of 0.924 with a p-value of 0.000. Conclusion: Nurse performance is related to patient satisfaction treated at the inpatient installation of Bhayangkara Hospital Jayapura. It is expected that the measurement of nurse performance with patient satisfaction will be carried out periodically, a maximum of once a year to evaluate nursing services.